HIV risk profile of male street youth involved in survival sex. Issue 6 (30th November 2004) - Haley, N; Roy, E; Leclerc, P; Boudreau, J-F; Boivin, J-F
Abstract : Objectives: To compare HIV risk factors of male street youth involved in survival sex with those of their never involved peers and to describe the sexual activities of the involved youths. Methods: From 2001 to 2003, street youth aged 14–23 years were recruited from street youth agencies in Montreal, Canada. Information was collected on sociodemographic characteristics, substance use, and sexual behaviours. Involvement in survival sex was defined as having ever exchanged sex for money, gifts, drugs, shelter, or other needs. Logistic regression was used to identify HIV risk factors associated with involvement in survival sex. Results: Among the 542 male participants recruited, 27.7% reported involvement in survival sex. HIV risk factors independently associated with such involvement were injection drug using partners (modulated by length of homelessness), unprotected oral sex with male partners, steroid injection, history of sexual abuse, and drug injection. Among involved youths, 32.0% had only female clients, 41.3% only male clients, and 26.7% had clients of both sexes. Unprotected sexual activities were common with clients. However, even more risks were taken with non-commercial sexual partners. Conclusions: Male street youth involved in survival sex are at higher risk for HIV than their non-involved peers not only because of their unprotected commercial sexual activities. They have multiple other HIV risks related to non-commercial sexual activities, drug injection, and sexual abuse. All these risks need to be addressed when providing sexual health interventions for this population.